Secondary amenorrhea in a case of gonadotropin independent precocious puberty: McCune-Albright syndrome - Subbiah, Sridhar; Nazirudeen, Roshan; Natarajan, Sundari; Vasanthiy, Vasanthiy; Jayaraman, Sangumani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Precocious puberty may be gonadotropin dependent or gonadotropin independent and due to a myriad of causes including syndromic association. McCune-Albright syndrome (MAS) is a rare disorder, characterized by the triad of precocious puberty, polyostotic fibrous dysplasia of bone and café-au-lait macules. Here, we describe a case of childhood onset gonadotropin independent precocious puberty who presented at 19 years of age with secondary amenorrhea. On detailed evaluation, she was found to have multiple café au lait spots and polyostotic fibrous dysplasia and diagnosis of MAS were made. Typically, the lesions of fibrous dysplasia are most active during childhood and adolescence, tending to become quiescent in adult life, new active lesions being rare in adults. In our case, despite fibrous dysplasia being asymptomatic on presentation, there were multiple active polyostotic lesions with bilateral encroachment of optic foramina, which is rare at this age. This case highlights the fact that careful examination for syndromic features and periodic follow up are important in all cases of precocious puberty.